Safety of Dapagliflozinin Reducing Cardiac Events and Deaths among NYHA Class II and III Cardiac Failure Patients. - Shabana Mohammad Ali (Pakistan Journal of Medical & Health Sciences, 2024)
Background: In last few decades, a global transition in incidence of heart failure with reduced ejection fraction from hypertension and valvular heart disease to coronary artery disease has taken place. Aim: To assess the safety of Dapagliflozin in reducing the cardiac events and deaths among class II and class III heart failure patients. Study design: Randomized controlled trial. Methodology: Cardiac patients (n=480) who belonged from class II and III with mild to moderate reduced ejection fraction were added in this study. This study was held at Cardiology Department at Mayo Hospital. All patients received sodium–glucose co-transporter-2 (SGLT2) inhibitors at a dose of 10mg once daily or matching placebo, in addition to usual therapy for eight weeks. SPSS-v25 analyzed the entered data. Mean ± SD presented age, blood pressure and eGFR level. Chi square test was used to compare the gender, NYHA class, primary composite outcome, and cardiovascular death. Results: Dapagliflozin showed lower rates of the primary composite outcome (15.8% vs. 23.3%, p = 0.038). There was no statistically significant difference in cardiovascular death between both groups (5.8% vs. 8.8%, p = 0.219). Practical Implication: Due to lack of research culture in our setups, common health issue like chronic heart failure remained clandestine. Present study highlighted the role of oral dapagliflozin in reducing worse cardiovascular events and deaths among NHY class II and III heart failure patients. Conclusion: It was concluded that dapagliflozin showed significant reductions in various cardiovascular events and deaths compared to placebo thus highlighting its potential as a beneficial intervention in our population. Keywords: Heart Failure, Reduced Ejection Fraction, NYHA Classification, Urgent Visits and Cardiac deaths.